UNA LONGITUD EN SECUENCIAS DE NUCLEÓTIDOS Y EL NÚMERO NULA - Rodríguez, L.; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2004)
A length over sequences of nucleotides is defined in similar way as is defined over permutations of the symmetric group. This length shows similar properties as the length for permutations and also shows some compatible properties with the three dimension representation defined in [1,2].